(untitled) (Universa Medicina, 2022)
Background Type 2 diabetes mellitus (T2DM) remains a public health problem in the world, including Indonesia. The high mortality of T2DM is triggered by an unhealthy eating pattern and sedentary lifestyle. We aimed to investigate the relationship of food intake pattern and its related factors with T2DM in adults 40 years and older. Methods This was a cross-sectional study conducted on 11,022 men and women with T2DM aged 40 years and older. Major dietary patterns were collected and multiple logistic regression analysis was used to determine the effect of covariates. Statistical significance was set at a p-value of <0.05. Results Males and individuals aged >40 years comprised 50.17% and 26.19%, respectively, of the 11,022 respondents. Individuals aged over 50 years had a higher risk of developing diabetes than those aged less than 50 years (AOR =5.67, 95% CI=1.37-21.94, p<0.05). Dietary processed meat was associated with a higher risk of T2DM (AOR = 4.9; 95% CI=1.08-22.20, p<0.05). Carbohydrate and fruit intakes were negatively associated with and protective factors for DM (AOR= 0.01; 95% CI=0.01-0.06, p<0.01; AOR = 0.35; 95% CI=0.15-0.83, p<0.01). However, physical activity was not a risk factor for T2DM. Conclusions Processed meat consumption, age over 50 years, and carbohydrate intake may increase the risk of T2DM in adults. Conversely, fruit intake may decrease the risk of T2DM in adults. There is a need to control the diet and lifestyle for the early prevention of DM.